Altered Global Brain Signal during Physiologic, Pharmacologic, and Pathologic States of Unconsciousness in Humans and Rats. (June 2020) - Tanabe, Sean; Huang, Zirui; Zhang, Jun; Chen, Yali; Fogel, Stuart; Doyon, Julien; Wu, Jinsong; Xu, Jianghui; Zhang, Jianfeng; Qin, Pengmin; Wu, Xuehai; Mao, Ying; et al.
Abstract : Background: Consciousness is supported by integrated brain activity across widespread functionally segregated networks. The functional magnetic resonance imaging–derived global brain signal is a candidate marker for a conscious state, and thus the authors hypothesized that unconsciousness would be accompanied by a loss of global temporal coordination, with specific patterns of decoupling between local regions and global activity differentiating among various unconscious states. Methods: Functional magnetic resonance imaging global signals were studied in physiologic, pharmacologic, and pathologic states of unconsciousness in human natural sleep (n = 9), propofol anesthesia (humans, n = 14; male rats, n = 12), and neuropathological patients (n = 21). The global signal amplitude as well as the correlation between global signal and signals of local voxels were quantified. The former reflects the net strength of global temporal coordination, and the latter yields global signal topography. Results: A profound reduction of global signal amplitude was seen consistently across the various unconscious states: wakefulness (median [1st, 3rd quartile], 0.46 [0.21, 0.50]) versus non-rapid eye movement stage 3 of sleep (0.30 [0.24, 0.32]; P = 0.035), wakefulness (0.36 [0.31, 0.42]) versus general anesthesia (0.25 [0.21, 0.28]; P = 0.001), healthy controls (0.30 [0.27, 0.37]) versus unresponsive wakefulness syndrome (0.22 [0.15, 0.24]; P < 0.001), and low dose (0.07 [0.06, 0.08]) versus high dose of propofol (0.04 [0.03, 0.05]; P = 0.028) in rats. Furthermore, non-rapid eye movement stage 3 of sleep was characterized by a decoupling of sensory and attention networks from the global network. General anesthesia and unresponsive wakefulness syndrome were characterized by a dissociation of the majority of functional networks from the global network. This decoupling, however, was dominated by distinct neuroanatomic foci ( e.g., precuneus and anterior cingulate cortices). Conclusions: The global temporal coordination of various modules across the brain may distinguish the coarse-grained state of consciousness versus unconsciousness, while the relationship between the global and local signals may define the particular qualities of a particular unconscious state. Abstract : Functional magnetic resonance imaging of global brain signal amplitude and functional connectivity demonstrates a strong association between overall brain connectivity and the level of consciousness in both humans and rats. Each distinct state of unconsciousness, including sleep, general anesthesia, and unresponsive wakefulness syndrome showed state-specific alterations in global signal topography. These findings suggest that the global temporal coordination defines the coarse-grained state of consciousness versus unconsciousness, while the relationship of the global and local signals defines the particular qualities of that unconscious state.